Questions kids ask about customs and traditions - Comely, Richard; Dickie, Alison (Grolier Toronto, 1989)
Questions Kids Ask About Customs and Traditions explores the rich diversity of cultural practices, answering children's curious inquiries about the origins, meanings, and variations of customs from different societies.